Surrogacy and ıts Legal Consequences According to the Legislation of Georgia - Kariauli, Nino (European Scientific Journal, ESJ, 2017)
The present article overviews surrogacy and its legal consequences according to the Georgian legislation, compares surrogacy legislation of common-law and continental countries and Georgian Legislation. Differences in legislation regulating surrigacy field in Georgia, EU countries and United States are emphezised. The main purpose of the present article is to introduce the main legal problems that we face in Georgian legislation regarding the surrogacy issue. For example, how Georgian legistalion ingnores the rights of a surrogate mother and a child’s interests; besides, how currently in forced Georgian legislaton promotes commercial surrogacy in Georgia, and a child becomes an object of trade in exchange for certain remuneration, while a surrogate mother or a gestational mother is only a device, a vessel for an embryo development and maintenance. I belive that such kind of articles will facilitate creation and develompnet of the legislation that will defence equal human rights and will secure not only “client parents ” rights, but also the rights of a surrogate mother and ta child and will interfere to etablish surrogacy as “cheap and profitable business” in Georgia.